The population features of visually impaired children aged between 0 and 14 in Hungary - Kiss, Erika; Pajor, Emese (Gyermeknevelés Tudományos Folyóirat, 2022)
This paper focuses on the crucial features of the healthcare and pedagogical services provided for 1,432 visually impaired (VI) children aged 0–14 who participated in an exploratory research project conducted between 2014 and 2019. In order to explore the population characteristics of visually impaired children in Hungary, the paper relies on two major data sources: the census data of the Hungarian Central Statistical Office between 1990-2016, and the examination documents of the Corps of Pedagogical Services of Visually Impaired Children from 2009 to 2013. The following data were analysed: the ratio of blind and low vision children in the various phases of special and majority educational institutions; the frequency of premature birth among blind and low vision children in relation to gestational weeks; the frequency of ophthalmologist diagnoses among groups of VI children; the frequency of ophthalmologist diagnoses among groups of VI children; associated disabilities of VI children. The results suggest that the population of visually impaired children is under transformation: visually impaired groups based on the classical interpretation of visual performance are being replaced by new groups governed by needs.